Applied Cancer Research - Gollob, Kenneth
Applied Cancer Research is an open access, peer-reviewed journal focused on clinical, surgical and translational research in the field of oncology. The journal considers for publication original articles addressing genetics, pathology, immuno-oncology, microbiome, bioinformatics, diagnosis, treatment, patient care, and population sciences of cancer. As a multidisciplinary journal, Applied Cancer Research aims to be a forum for exchanging relevant information among researchers, health care practitioners and health policy makers, helping them enhance prevention and decrease mortality rates from malignant diseases, improve the management of patients afflicted by them and the quality of life of people during and after treatment.